2000
DOI: 10.1016/s0022-3093(99)00942-4
|View full text |Cite
|
Sign up to set email alerts
|

Thin film transistors obtained by hot wire CVD

Abstract: Hydrogenated microcrystalline silicon films obtained at low temperature (150ºC-280ºC) by hot-wire chemical vapour deposition at two different process pressures were measured by Raman spectroscopy, X-ray diffraction spectroscopy and photothermal deflection spectroscopy.A high crystalline fraction (> 90%) with a low subgap optical absortion (10 cm -1 at 0.8 eV) were obtained in films deposited at high growth rates (>0.8 nm/s). These films were incorporated in nchannel thin film transistors and their electrical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Hot-Wire Chemical Vapour Deposition (HWCVD) technique has shown its ability to obtain hydrogenated amorphous and nanocrystalline silicon thin-film transistors (TFT) at low substrate temperatures (<200 ºC) with acceptable field-effect mobilities and threshold voltages [1,2]. Besides, improved stabilities of these devices compared to their counterparts deposited by Plasma-Enhanced Chemical Vapour Deposition (PECVD) have been reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Hot-Wire Chemical Vapour Deposition (HWCVD) technique has shown its ability to obtain hydrogenated amorphous and nanocrystalline silicon thin-film transistors (TFT) at low substrate temperatures (<200 ºC) with acceptable field-effect mobilities and threshold voltages [1,2]. Besides, improved stabilities of these devices compared to their counterparts deposited by Plasma-Enhanced Chemical Vapour Deposition (PECVD) have been reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…The first low-temperature amorphous thin film transistors ͑TFTs͒ reported were deposited on glass at 150°C by Feng et al, 2 and at 125°C ͑with no n ϩ contacts͒ by McCormick et al 3 Recently, the first TFTs on plastic were fabricated, at 125°C on polycarbonate by Gates,4 at 150°C on polyimide by Glaskova et al, 5 and at 110°C on polyethylene terephthalate by C.-S. Yang et al 6 The layers for the devices produced at 125°C were deposited by rf reactive magnetron sputtering while those produced at 150°C and 110°C used rf plasma-enhanced chemical vapor deposition ͑rf-PECVD͒. [8][9][10][11] It is the high efficiency of the hot tungsten filament in breaking the molecules of the reactant gases, together with a high atomic hydrogen supply to the growing film, that is thought to allow the deposition of good quality amorphous and microcrystalline silicon films at a high growth rate by HW. For industrial applications, a high growth rate is attractive from a cost perspective because it decreases the process time and may increase the utilization efficiency of the process gases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, thermionic emission over these energy barriers is usually considered as the major conduction mechanism when dealing with poly-Si, and our recent simulation results have shown that thermionic conduction indeed describes the transfer and output characteristics of the proposed device well at room T [14]. This kind of thermally activated process also manifests itself in a way that the mobility and V TH decrease and increase, respectively, as T is reduced [15,16]. Transfer curves in the SG-1 mode, shown in figure 4(a), are clearly consistent with the above statements.…”
Section: Electrical Characteristicsmentioning
confidence: 60%